The Influence of Creative Problem-Solving Learning Assisted by Ethnomathematics Nuance Modules on Problem-Solving Ability and Curiosity - Ida Fitri Kurnia; Suparman; Topan Rahmatul Iman (Poltanesa, 2023)
Mathematics is often perceived as a complex and difficult lesson to solve, thus making students' mathematical problem-solving ability and curiosity low. This study aimed to analyze the influence of learning using the Creative Problem-Solving (CPS) method assisted by ethnomathematics nuance modules on the problem-solving ability and curiosity of class XI students at SMAN 1 Plampang. This research was a type of experimental research using a pre-experimental design with a one-group pretest–post–test design model. The data collection technique used purposive sampling to collect data as a sample of 35 students in class XI MIPA 1 from a total population of 105 students in class MIPA. The determination of the sample is based on the results of the average score in mathematics and discussion with the mathematics teacher. The results of the study showed that the influence of Creative Problem Solving (CPS) learning assisted by ethnomathematics nuance modules had a significant effect on students' problem-solving ability and students' curiosity in geometry transformation material at SMAN 1 Plampang.